The Influence of Work Environment, Compensation, and Career Development on Employee Retention at PT. Waskita Beton Precast Sales Area 3 Surabaya - Christoforus David Kurniawan; Acep Samsudin (International Journal of Social, Economic, and Business, 2025)
This study aims to analyze the influence of work environment, compensation, and career development on employee retention. The object of this research is PT. Waskita Beton Precast Sales Area 3 Surabaya. The research method employs a quantitative approach. Data were collected through questionnaires and analyzed using multiple linear regression. The research sample consists of employees of PT. WSBP Sales Area 3 Surabaya. The results show that simultaneously, the work environment, compensation, and career development have a positive and significant influence on employee retention. Partially, each of the three independent variables also demonstrates a significant influence on the employee retention variable. Therefore, it can be concluded that improving the quality of the work environment, providing appropriate compensation, and offering clear career development opportunities can enhance employee retention. This research provides practical implications for the company in formulating human resource management strategies to reduce employee turnover.